ESL Learners Use of English Modals in Narrative Compositions: Syntatic and Semantic Accuracy - Malachi Edwin Vethamani; Umi Kalthom Abd Manaf; Omid Akbari (TEFLIN, 2008)
This study investigated use of modals in two written tasks by Form 4 Malaysian secondary school ESL learners. The aim was to investigate the use of English modals at the syntactic and semantic levels from data made available by the EMAS Corpus.ÃÂ ÃÂ The research design comprised a qualitative technique through discourse analysis supplemented with some descriptive statistics derived from a concordancer. The concordancer identified modals used by the students at the form 4 level. The research findings showed that two modals not stipulated in the syllabus, would and shall, were also found in the narrative compositions. The secondary school English language syllabus indicated varied meanings to the modals, but it was found that students repetitively used only a few of the same modals for these various functions. It was concluded that there were some inadequacies in the syllabus that led to the problems encountered by ESL students.ÃÂ In order to circumvent the problematic items identified in the study, and to further improve the teaching and learning of modal auxiliaries among ESL learners, several recommendations are proposed.